2019
DOI: 10.1161/circulationaha.118.038924
|View full text |Cite
|
Sign up to set email alerts
|

Spliced X-box Binding Protein 1 Stimulates Adaptive Growth Through Activation of mTOR

Abstract: Background: The unfolded protein response plays versatile roles in physiology and pathophysiology. Its connection to cell growth, however, remains elusive. Here, we sought to define the role of unfolded protein response in the regulation of cardiomyocyte growth in the heart. Methods: We used both gain- and loss-of-function approaches to genetically manipulate XBP1s (spliced X-box binding protein 1), the most conserved signaling branch of the unfolded pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…We first determined whether the HBP enzymes were altered in cultured cardiomyocytes by hypertrophic stimuli in a time course study. Phenylephrine (PE) is an agonist for α1 adrenergic receptor, which is commonly used to stimulate cardiomyocyte hypertrophic growth in vitro [28][29][30] . We isolated and cultured primary neonatal rat ventricular myocytes (NRVMs) from 1 to 2 days old Sprague-Dawley rats as before 9,31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first determined whether the HBP enzymes were altered in cultured cardiomyocytes by hypertrophic stimuli in a time course study. Phenylephrine (PE) is an agonist for α1 adrenergic receptor, which is commonly used to stimulate cardiomyocyte hypertrophic growth in vitro [28][29][30] . We isolated and cultured primary neonatal rat ventricular myocytes (NRVMs) from 1 to 2 days old Sprague-Dawley rats as before 9,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon removal of doxycycline from drinking water, tTA was activated and Gfat1 was induced only in cardiomyocytes. We have previously applied this inducible approach in the heart 9,30 , the liver 35 , and the adipose tissue 36 , which represents a tight, efficient, and reproducible means to genetically manipulate gene expression. We supplemented doxycycline (0.1 mg/L) in drinking water during breeding, pregnancy, and weaning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was shown that XBP1 s is protective in a novel murine model of HFpEF via its ability to induce those same proteins involved in O-GlcNAcylation [69]. XBP1 s has an additional role in regulating cardiac hypertrophy in response to pressure-overload via transcriptional induction of FKBP11, and thus regulating mTORC1 activity [94].…”
Section: Er Uprmentioning
confidence: 99%
“…Moreover, inhibition of O-GlyNAcases increased mitochondrial OXPHOS enzyme activities, implying that this is one way that O-GlcNAcylation might be protective (35); however, the mechanism by which XBP1-mediated protein O-GlcNAcylation results in cardioprotection remains unclear. In terms of heart failure, it was shown that XBP1s stimulates adaptive cardiac growth through activation of mTORC1, which is mediated via FKBP11 (FK506-binding protein 11), a novel transcriptional target of XBP1s, thus describing a non-canonical protective for IRE1/XBP1s in pathological hypertrophy (Figure 2A, IRE1/XBPs cardiac hypertrophy) (36). It has also been shown that in a mouse model of heart failure with preserved ejection fraction (HFpEF), activation of IRE1 is deficient and restoration of activated XBP1 ameliorated the HFpEF phenotype (37).…”
Section: Er Proteostasis In Cardiac Pathologymentioning
confidence: 99%